The aspartate aminotransferase-to-alanine aminotransferase ratio predicts all-cause and cardiovascular mortality in patients with type 2 diabetes. Issue 43 (October 2016) - Zoppini, Giacomo; Cacciatori, Vittorio; Negri, Carlo; Stoico, Vincenzo; Lippi, Giuseppe; Targher, Giovanni; Bonora, Enzo
Abstract : Abstract: An increased aspartate aminotransferase-to-alanine aminotransferase ratio (AAR) has been widely used as a marker of advanced hepatic fibrosis. Increased AAR was also shown to be significantly associated with the risk of developing cardiovascular (CV) disease. The aim of this study was to assess the relationship between the AAR and mortality risk in a well-characterized cohort of patients with type 2 diabetes. A cohort of 2529 type 2 diabetic outpatients was followed-up for 6 years to collect cause-specific mortality. Cox regression analyses were modeled to estimate the independent association between AAR and the risk of all-cause and CV mortality. Over the 6-year follow-up period, 12.1% of patients died, 47.5% of whom from CV causes. An increased AAR, but not its individual components, was significantly associated with an increased risk of all-cause (adjusted-hazard risk 1.83, confidence interval [CI] 95% 1.14–2.93, P = 0.012) and CV (adjusted-hazard risk 2.60, CI 95% 1.38–4.90, P  < 0.003) mortality after adjustment for multiple clinical risk factors and potential confounding variables. The AAR was independently associated with an increased risk of both all-cause and CV mortality in patients with type 2 diabetes. These findings suggest that an increased AAR may reflect more systemic derangements that are not simply limited to liver damage. Further studies are needed to elucidate the pathophysiological implications of an increased AAR.